Decision support system for set-up of investment portfolio as a part of company development program - Moskalenko, V.; Kachanova, S. (М. О. Бондаренко, 2018)
The analysis carried out in this paper describes the functionality of existing investment decision support systems. A business process for the formation of an investment portfolio as part of the company development program was proposed. The portfolio consists of three parts: a portfolio of development projects of the company, a portfolio of projects of other companies and a portfolio of securities. The architectural solution for the software implementation of the decision support system in the field of portfolio investment is presented. It is proposed to present the DSS for the formation of an investment portfolio in the form of five containers, in which the corresponding tasks are performed: evaluation of investment projects; evaluation of securities; Assessment of the importance of investments for the development of the company; allocation of the company investment funds between portfolios; formation of the company investment portfolio. This decision support system is associated with Enterprise Performance Management systems which are designed for information and analytical support of strategic company management processes. Implementing of DSS that the user can solve package investment problems for making certain investment decisions and solve them in package for implementing the company development program during the strategic period.
Keywords: investment; decision support system; software architecture; service-oriented architecture